School Counselors' Perceptions of School Shooting Causes and Protocols. Issue 3 (1st September 2020) - Hicks, Janet; Carter, Stacy L.; Berry, Steve; Noble, Nicole; Winkelman, Logan; Bonner, Layla
ABSTRACT: In order to ascertain school counselors' beliefs regarding the causes of and strategies for preventing school shootings, 50 school counselors participated in a qualitative survey. The survey used Content Analysis to organize and analyze the school counselors' responses into themes that represented their beliefs about school shootings. Overwhelmingly, the school counselors supported the provision of counseling services as a means to prevent school shootings and also supported some school security measures, as well as educational interventions targeting relationship building. The relevance of these findings are discussed in relation to current research and position statements on the causes and prevention of school shootings.